2013
DOI: 10.1017/s0007114512005880
|View full text |Cite
|
Sign up to set email alerts
|

Infant neurocognitive development is independent of the use of iodised salt or iodine supplements given during pregnancy

Abstract: The benefits of iodine supplements during pregnancy remain controversial in areas with a mild-to-moderate iodine deficiency. The aim of the present study was to determine the effect of improving iodine intakes, with iodised salt (IS) or iodine supplements, in pregnant Spanish women. A total of 131 pregnant women in their first trimester were randomly assigned to three groups: (1) IS in cooking and at the table, (2) 200 mg potassium iodide (KI)/d or (3) 300 mg KI/d. No differences were found in thyroid-stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
61
0
10

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 32 publications
(61 reference statements)
5
61
0
10
Order By: Relevance
“…One of the studies (80) assessed Tg concentration in the first trimester before supplementation and then again at two weeks postpartum; one study (81) assessed Tg in the first and third trimesters; and one study (82) assessed Tg in all three trimesters and again 12-24 weeks postpartum. Tg concentrations in women in the first trimester (i.e., at baseline before supplementation) ranged from 13 to 25 lg/L, and postpartum, in women that had received any type of additional iodine (i.e., supplements or iodized salt), Tg ranged from 8 to 18 lg/L.…”
Section: Pregnant Womenmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the studies (80) assessed Tg concentration in the first trimester before supplementation and then again at two weeks postpartum; one study (81) assessed Tg in the first and third trimesters; and one study (82) assessed Tg in all three trimesters and again 12-24 weeks postpartum. Tg concentrations in women in the first trimester (i.e., at baseline before supplementation) ranged from 13 to 25 lg/L, and postpartum, in women that had received any type of additional iodine (i.e., supplements or iodized salt), Tg ranged from 8 to 18 lg/L.…”
Section: Pregnant Womenmentioning
confidence: 99%
“…Tg concentrations in women in the first trimester (i.e., at baseline before supplementation) ranged from 13 to 25 lg/L, and postpartum, in women that had received any type of additional iodine (i.e., supplements or iodized salt), Tg ranged from 8 to 18 lg/L. Of the two studies with postpartum data (80,82), only one study (80) reported that women taking iodine supplementation in pregnancy had a postpartum median Tg <13 lg/L. However, the interpretation of these findings is confounded by differences in study designs, including a lack of a placebo group, relatively small sample sizes (n = 66-131), varying levels and types of supplemental iodine (iodized salt or supplements containing 150-300 lg iodine per day), duration of follow-up (2-24 weeks postpartum), and use of different Tg assays.…”
Section: Pregnant Womenmentioning
confidence: 99%
“…Nine RCTs (24,25,26,27,28,29,30,31,32) and eight observational studies (33,34,35,36,37,38,39,40) were included in the review. Seven RCTs were reported on the effects of maternal supplementation on maternal thyroid function (26,27,28,29,30,31,32,33,34,35,36,37,38,39,40). Of these, four RCTs also contained data on neonatal thyroid function (27,29,30,32).…”
Section: Study Selectionmentioning
confidence: 99%
“…Seven RCTs were reported on the effects of maternal supplementation on maternal thyroid function (26,27,28,29,30,31,32,33,34,35,36,37,38,39,40). Of these, four RCTs also contained data on neonatal thyroid function (27,29,30,32). One RCT (32) and four observational studies (33,36,39,40) addressed the impact of gestational iodine supplementation on infant neuropsychological function, while two RCTs investigated the impact of iodine supplementation on cognitive performance in school-age children (24,25).…”
Section: Study Selectionmentioning
confidence: 99%
“…Velasco et al also found an increase of neonatal TSH in a group of pregnant women receiving 50-200 μg of iodine daily, but based on psychomotor tests performed at 3-18 months of age he also showed that iodine supplementation positively influenced on the neurological development of children [30]. However, recently these authors did not observe the positive impact of iodine supplementation during pregnancy on infant neurocognitive development [31], whereas Rebagliato et al showed decreased psychomotor and mental index scores of infants in the first year of life, whose mothers consumed ≥ 150 μg/day of iodine from supplements [32]. The vast majority of our subjects were women with autoimmune thyroid diseases.…”
Section: Prace Oryginalnementioning
confidence: 97%